1996
DOI: 10.1577/1548-8675(1996)016<0357:omortc>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Observed Mortality of Rainbow Trout Caught by Different Angling Techniques in Lake Taupo, New Zealand

Abstract: Angling mortality was assessed for Lake Taupo wild rainbow trout Oncorhynchus mykiss caught by four different trolling techniques and released. Observed cumulative mortalities 48–53 h after hooking were 15.3% for downrigger, 14.0% for wire line, 7.8% for lead line, and 2.2% for harling. Both immediate and delayed mortalities for each method are discussed. Ninety‐three percent of the total mortality occurred within 26 h after release. Hooking injuries, playing time, transit time, depth at capture, and fish leng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Physical and physiological factors of concern include the extent of exertion during playing and landing, the physical effect of hooking and handling the fish, exposure of fish within keepnets to harmful deterioration in water quality, and the possible initiation of a physiological stress response consequent to the combined effects of capture, handling, restraint and confinement. Some information is available regarding the welfare of individual fish and the effects of angling pressure on populations of fish (Brana et al, 1992;Brobbel et al, 1996) and there are limited data available concerning mortality arising from hook damage (Bugley & Shepherd, 1991;Dedual, 1996;Dextrase & Ball, 1991;Muoneke & Childress, 1994;Malchoff & Heins, 1997) and the recovery of rod-caught fish post-capture (Ferguson & Tufts, 1992;Pankhurst & Dedual, 1994;Wilkie et al, 1996). However, the species and conditions employed in these studies are not strictly relevant to United Kingdom non-salmonid fisheries, in which catch-and-return angling is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and physiological factors of concern include the extent of exertion during playing and landing, the physical effect of hooking and handling the fish, exposure of fish within keepnets to harmful deterioration in water quality, and the possible initiation of a physiological stress response consequent to the combined effects of capture, handling, restraint and confinement. Some information is available regarding the welfare of individual fish and the effects of angling pressure on populations of fish (Brana et al, 1992;Brobbel et al, 1996) and there are limited data available concerning mortality arising from hook damage (Bugley & Shepherd, 1991;Dedual, 1996;Dextrase & Ball, 1991;Muoneke & Childress, 1994;Malchoff & Heins, 1997) and the recovery of rod-caught fish post-capture (Ferguson & Tufts, 1992;Pankhurst & Dedual, 1994;Wilkie et al, 1996). However, the species and conditions employed in these studies are not strictly relevant to United Kingdom non-salmonid fisheries, in which catch-and-return angling is prevalent.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a mortality rate of <1% represents one of the lowest mortality rates observed for any freshwater fish (Reviewed in Muoneke and Childress, 1994;Bartholomew and Bohnsack, 2005;Arlinghaus et al, 2007), and particularly low for salmonids (Taylor and White, 1992). One of the only other studies to evaluate immediate hooking mortality for lentic salmonids captured while trolling revealed that mortality rates ranged between 0 and 11.5% for four different trolling methods targeting rainbow trout in Lake Taupo, New Zealand (Dedual, 1996). Although none of the techniques are directly comparable to those used in the present study, they emphasize that subtle differences in technique can alter mortality estimates.…”
Section: Resultsmentioning
confidence: 56%
“…In the present study fish were captured at relatively shallow depths and no evidence of barotrauma was observed. By contrast, the only other freshwater trolling that involved anglers targeting salmonids recorded barotrauma in fish caught from greater depths (Dedual, 1996). Fish that fought for longer periods were more likely to lose equilibrium upon landing, but those also tended to be the largest fish.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations